The effect of cupping on calf muscles on the menstrual bleeding in patients with polycystic ovary syndrome - Mahnaz Yavangi; Azam Meyari; Mahdi Biglarkhani (Mashhad University of Medical Sciences, 2023)
Introduction: Polycystic ovary syndrome is one of the common diseases during the reproductive period that the common treatments are mostly symptomatic and their long-term use has many complications. According to previous studies that showed the effect of wet cupping on calf muscles on oligomenorrhea pattern, this study was performed with aim to investigate the effect of wet cupping on calf muscles on clinical and laboratory symptoms and quality of life in patients with this syndrome. Methods: In this randomized clinical trial study which was performed in 2019-2021, 60 PCOS women with minimum 60 days menstrual cycle entered the study and randomly divided to cupping and control groups (n=30 per group). At the 26th day menstrual cycle, after blood sampling for two groups, wet-cupping on calf muscles was done for intervention group. Menstrual period, insulin resistance and quality of life were measured using Cronin PCOS Questionnaire. Data analysis was done using SPSS statistical software (version 20) and student t and chi-square tests. P<0.05 was considered significant. Results: In this study, 21 members of cupping group and 6 members of control group menstruated after the intervention, the difference was statistically significant (p<0.001). Insulin resistance changed significantly in the intervention group (p=0.03). Quality of life was significantly improved in the cupping group (p=0.01), but no significant statistical difference was observed in the control group. Conclusion: Calf muscles wet-cupping can be considered as one of the options for causing bleeding in people with PCOS. Obviously, more studies are necessary to compare different protocols and investigate its mechanism.